Creative Character Development Through Drawing Activities in Elementary Students: Pengembangan Karakter Kreatif Melalui Aktivitas Menggambar pada Siswa Sekolah Dasar - Putra, Yudhistiral Pradana; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines creativity development within elementary education contexts. General Background: Creativity constitutes a central component of character formation and learning processes in primary schools, particularly within arts-based instructional settings aligned with the Profil Pelajar Pancasila framework. Specific Background: Classroom observations revealed that students’ drawing activities often lacked originality and independent idea generation, indicating limited creative expression during project-based learning implementation. Knowledge Gap: Although prior studies discuss character education and creative learning models, limited empirical classroom-based research explicitly analyzes drawing activities as a structured medium for strengthening creative character within the P5 framework. Aims: This research aims to analyze how drawing-based project activities contribute to students’ creative character formation. Results: Findings indicate observable improvements in originality, participation, and student engagement during successive instructional cycles, reflected through qualitative observation and documented student work. Novelty: The study positions structured drawing practice as a concrete operationalization of creative character indicators within project-based curricular implementation. Implications: These findings provide practical pedagogical guidance for elementary educators in integrating structured artistic exploration into character education programs while maintaining alignment with national curriculum directives. Keywords: Creative Character, Drawing Activities, Elementary Education, Project Based Learning, Profil Pelajar Pancasila Key Findings Highlights Progressive originality growth observed across instructional cycles Increased active classroom participation during project implementation Documented improvement in student-generated visual concepts